Phase II study of stereotactic radiosurgery for the treatment of patients with oligoprogression on erlotinib. (2019) - Weiss, Jared; Kavanagh, Brian; Deal, Allison; Villaruz, Liza; Stevenson, James; Camidge, Ross; Borghaei, Hossein; West, Jack; Kirpalani, Padmini; Morris, David; Lee, Carrie; Pecot, Chad V.; et al.
Abstract: Introduction: Retrospective studies have evaluated the approach of stereotactic radiotherapy (SRT) to address oligoprogression in patients with EGFR mutant NSCLC on TKI therapy, it has never been prospectively studied. Materials and methods: We treated 25 patients with EGFR mutant NSCLC on erlotinib who had 3 or fewer sites of extra-cranial progression with SRT to progressing sites, followed by re-initiation of erlotinib. Results: Median PFS from the initiation of SRT was 6 months (95% CI 2.5 to 11.6) and median OS was 29 months (95% CI 21.7 to 36.3). Neither baseline nor changes in the Veristrat proteomic predicted PFS. Conclusions: SRT and TKI continuation may be considered for select patients with EGFR mutant NSCLC and oligo-progression on EGFR TKI therapy.